Plant traits and community composition drive the assembly processes of abundant and rare fungi across deserts - Wang, Jianming; Qu, Mengjun; Wang, Yin; He, Nianpeng; Li, Jingwen (Frontiers in Microbiology, 2022)
The difference in community assembly mechanisms between rare and abundant fungi in deserts remains unknown. Hence, we compared the distribution patterns of abundant and rare fungi, and assessed the factors driving their assembly mechanisms across major desert habitats of China. Abundant fungal assembly was more affected by neutral processes than the rare. Null model and VPA analysis indicated that heterogeneous selection and dispersal limitation together dominated abundant fungal assembly, whereas rare fungal assembly was more influenced by heterogeneous selection. As a result, abundant sub-communities exhibited a higher species turnover rate than the rare. Hierarchical partitioning analysis indicated that soil conditions and plant attributes drove the assembly processes of abundant and rare fungi, respectively. Meanwhile, the relative strength of different assembly processes differed significantly among four vegetation types. In addition, we found that plant functional traits and composition played more critical roles in shaping the assembly processes of rare fungi than those of abundant fungi. Taken together, our findings collectively suggest that rare and abundant fungi exhibit differential ecological patterns that are driven by distinct assembly processes in deserts. We emphasize that the assembly processes of abundant and rare fungi are dependent on different abiotic and biotic factors in desert ecosystems.